Partial edentulism and its correlation with educational status: a hospitalbased study - Kaphle, Bhumesh; Shrestha, Ashish; Bhagat, Tarakant; Shrestha, Daniel; Bhandari, Suresh; Jha, Umesh (Journal of Karnali Academy of Health Sciences, 2020)
Background: Maintenance of oral hygiene is one of the most important factors to prevent tooth loss. Education plays a significant role to maintain good oral hygiene. The objective of the study was to determine partial edentulism based on Kennedy’s classification and to find out correlation between partial edentulism and educational status.Methods: A cross-sectional study was carried out among 189 partially edentulous patients visiting dental OPD of three government hospitals. Patients above 18 years of age were selected using non-probability convenience sampling, 63 from each center. History taking and visual examination were done after getting informed consent from the participants. Descriptive (mean, median, standard deviation, range, ratio and percentage) and inferential (Man-Whitney test) statistics were applied.Results: In 189 partially edentulous patients 61% were females and 39% were males, and 48.1% people had no formal education. Kennedy’s Class III was most common (59% in maxillary, 61% in mandibular arches) and Kennedy’s class IV was least common (1% in maxillary, 6% in mandibular arches). From the study, we found that the number of teeth missing was higher in people with no formal education and there was statistically significant difference in the number of missing teeth in people with formal education and people who didn’t have any formal education (p